Autologous blood transfusion. The effect of a microtransfusion of 225 mL autologous blood on 650-kcal time trial performance and an autologous blood transfusion of 675 mL on 4 x 30-s all-out cycling performance in well-trained, male rndurance athletes - Solheim, S. A. (Universität Kopenhagen, 2016)
Background: Autologous blood transfusion (ABT) is prohibited by the World Anti-Doping Agency (WADA) due to its ability to enhance endurance performance. However, the effect of a micro-ABT on endurance performance and the impact of a conventional ABT on repeated sprint performance have never been examined. Hypotheses: In well-trained, male endurance athletes a micro-ABT (225 mL) increases mean power (MP) and reduces elapsed time in a 650-kcal time trial (650-kcal TT), and a conventional ABT (675 mL) increases sprint-MP and MP in total for a 4 x 30-s all-out cycle test (RWAnT). Methods: In Part A, the reliability of the 650-kcal TT and RWAnT was tested in a random population, and results used to calculate the Minimal Difference to be considered real (MD) for evaluation of clinical significance in addition to statistical significance in Part B. In Part B, 6 welltrained male athletes underwent a placebo and ABT intervention in a randomized counterbalanced double-blind crossover design, separated by . 3 months. 900 mL of whole blood was drawn, and red blood cells (RBCs) stored (1.06 g RBCs per mL SAG-M) at 4 C for 4 wk. Participants received 675 mL of the withdrawn blood in two transfusions (225 mL and 450 mL) separated by 24 h. VO2peak was determined through a graded exercise test to exhaustion, and hematological parameters by blood analysis (e.g. [Hb], Hct, %Ret) and optimized CO-rebreathing (Hbmass). Changes in outcomes were evaluated from pre- to post-ABT. Results: The major findings were: (1) improved 650-kcal TT performance 2 h following micro-ABT (MP 5.1%, elapsed time -4.9%), and (2) progressively enlargement of the Delta MP for the ABT group with increasing sprint number, and an interaction between "Intervention" and "Sprint number" (p = 0.031). Conclusion: Within the limitations of this investigation, it appears that a 225 mL micro-ABT enhances 650-kcal TT performance, and that a 675 mL ABT improves 4 x 30-s all-out cycling test performance, at least in well-trained, male endurance athletes. The study call for further research towards the effect of micro- and conventional ABTs on endurance and repeated sprint performance, and highlights the importance of a high level of measurement standardization. The results provide new insight into the performance enhancing effects of ABT, and will potentially help anti-doping authorities in planning intelligent testing.